2019
DOI: 10.1177/0004867419836031
|View full text |Cite
|
Sign up to set email alerts
|

Altered social cognition and connectivity of default mode networks in the co-occurrence of autistic spectrum disorder and attention deficit hyperactivity disorder

Abstract: Objective: As two common neurodevelopmental disorders, autistic spectrum disorder and attention deficit hyperactivity disorder frequently occur together. Until now, only a few studies have investigated the co-occurrence of attention deficit hyperactivity disorder and autistic spectrum disorder, this is due to restrictions associated with previous Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision. Most previous research has focused on the developmental trajectories for autist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 53 publications
(59 reference statements)
1
26
0
Order By: Relevance
“…Figure 1 provides a schematic representation of findings from all the studies for each group, with yellow dots representing the DMN hub regions, blue (underconnected) or red (overconnected) dots representing connectivity with other brain regions, and thickness of lines connecting the dots representing frequency of findings across studies in each group. Here, we see that studies examining within-DMN connectivity (intra-DMN) found underconnectivity involving the posterior hub of the DMN or between the anterior and posterior hubs of the DMN more frequently in ASD (77,78,80,82,83,85,87,88,90,91,97,102,103), while overconnectivity involving the anterior hub or between the anterior and posterior hubs of the DMN was often found in EOP studies (105,109,112,113,117). Some studies reported intra-DMN underconnectivity in EOP involving the posterior hub of the DMN or between the medial and lateral hubs of the DMN (106,108,110,117).…”
Section: Dmn Connectivity In Adolescents With Eopmentioning
confidence: 71%
“…Figure 1 provides a schematic representation of findings from all the studies for each group, with yellow dots representing the DMN hub regions, blue (underconnected) or red (overconnected) dots representing connectivity with other brain regions, and thickness of lines connecting the dots representing frequency of findings across studies in each group. Here, we see that studies examining within-DMN connectivity (intra-DMN) found underconnectivity involving the posterior hub of the DMN or between the anterior and posterior hubs of the DMN more frequently in ASD (77,78,80,82,83,85,87,88,90,91,97,102,103), while overconnectivity involving the anterior hub or between the anterior and posterior hubs of the DMN was often found in EOP studies (105,109,112,113,117). Some studies reported intra-DMN underconnectivity in EOP involving the posterior hub of the DMN or between the medial and lateral hubs of the DMN (106,108,110,117).…”
Section: Dmn Connectivity In Adolescents With Eopmentioning
confidence: 71%
“…Approximately 52% of the studies in adolescents with ASD presented in our review (Table 1 and 2) have utilized the ABIDE dataset to investigate DMN connectivity (Nielsen et al, 2014;Nomi and Uddin, 2015;Elton et al, 2016;Falahpour et al, 2016;Ypma et al, 2016;Chen et al, 2017;Guo et al, 2017;Bi et al, 2018;Kernbach et al, 2018;Borras-Ferris et al, 2019;Guo et al, 2019;Lawrence et al, 2019;Reiter et al, 2019;Wang et al, 2019a). About half of the studies (15 out of 29) in adolescents with ASD have found a global pattern of underconnectivity both within the DMN hubs (Assaf et al, 2010;Weng et al, 2010;Starck et al, 2013;Falahpour et al, 2016;Ypma et al, 2016;Neufeld et al, 2018;Borras-Ferris et al, 2019;Reiter et al, 2019), as well as between the DMN and other brain regions such as insula, subcortical regions, fronto-parietal regions, and visual cortex (Wiggins et al, 2011;Nielsen et al, 2014;Nomi and Uddin, 2015;Kernbach et al, 2018;Guo et al, 2019), regardless of analytic methods used.…”
Section: Dmn Connectivity In Adolescents With Asdmentioning
confidence: 99%
“…Relatively fewer studies (five out of 29) have observed over-connectivity between the DMN and task-positive regions within the frontoparietal, visual, and sensorimotor regions, as well as the salience network (Redcay et al, 2013;Elton et al, 2016;Hogeveen et al, 2018;Gao et al, 2019;Mash et al, 2019). Some studies (nine out of 29) have additionally found mixed patterns involving under-and over-connectivity of ASD youth relative to typically developing (TD) controls, largely highlighting a pattern of within-DMN underconnectivity, with overconnectivity between DMN and other networks such as task-positive or sensorimotor networks (Doyle-Thomas et al, 2015;Jann et al, 2015;Abbott et al, 2016;Chen et al, 2017;Guo et al, 2017;Joshi et al, 2017;Bi et al, 2018;Pereira et al, 2018;Lawrence et al, 2019;Wang et al, 2019a). This mixed pattern of connectivity may suggest poor integration within the DMN, along with atypical segregation between the DMN and other related cognitive networks in adolescents with ASD (see Table 2 for main results from each study).…”
Section: Dmn Connectivity In Adolescents With Asdmentioning
confidence: 99%
See 2 more Smart Citations